Anaesthetic issues in Brugada electrocardiogram/syndrome undergoing laproscopic common bile duct exploration and laproscopic primary common bile duct closure - Shrestha, BR; Joshi, M R; Bohara, T P (Journal of Kathmandu Medical College, 2014)
Here we report a rare case of Brugada Syndrome in a young Nepalese male undergoing laparoscopic common bile ductexploration and laparoscopic primary common bile duct closure. Recognition of the disease, preparedness to tacklethe developing arrhythmias, avoidance of precipitating drugs, adopting policy of anaesthetic interventions to balancethe autonomic system, maintenance of normothermia and electrolyte balance, avoidance of hypoxia, hypercarbia andacidosis are the key to management of this disease in anaesthetic pursuit. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10555 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, Page: 36-39